Implementation of shear thinning behavior in the fused filament fabrication melting model: Analytical solution and experimental validation - Colón Quintana, José Luis; Hiemer, Stefan; Granda Duarte, Nancy; Osswald, Tim (Additive Manufacturing, 2020)
Fused Filament Fabrication (FFF) has been on the forefront of Additive Manufacturing (AM) due to low costs, ability to manufacture complex geometries, and broad availability of AM machines in the market. Various theoretical models have been proposed to explain the melting behavior of the polymer filament in the FFF process. The most prevalent model involves the formation of a pool of polymer melt at the nozzle that is pushed out of the orifice by the solid filament acting as a piston (Bellini et al., 2004) [1]. An alternative model that suggests the formation of a melt film, with thickness varying as a function of the force exerted by the solid filament, is used as basis for this work. This model, known as the "Fused Filament Fabrication melting model", was proposed by Osswald et al. (2018) [2] and assumes a Newtonian fluid, which is a simplification of the real rheological behavior of polymeric melts. This work aims to improve this model by implementing the shear thinning behavior of the material into the equations. The analytical solution of the shear thinning model is compared to models found in literature using experimental data at different printing conditions. By comparing these models, it was shown that the implementation of shear thinning effects enhances the prediction of the melting behavior of the filament material at both low and high printing temperatures using the corresponding assumptions.
CRIS-Team Scopus Importer:2020-12-04